IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE PARAGRAPH THROUGH SIMULTANEOUS ROUNDTBLE STRATEGY - Yudhi Pratama Tarigan; Yunita Agnes Sianipar (Universitas Negeri Medan, 2014)
ABSTRACT This study attempts to improve students’ achievement in writing descriptive paragraph through simultaneous roundtable strategy. This study was conducted by using classroom action research. The subject of the research was class VIII-5 SMP N 2 Berastagi consisting of 30 students. The research was conducted in two cycles and consisted of seven meetings. The instruments for collecting data were writing tests as the quantitative data and diary notes, observation sheet, and questionnaire sheet as qualitative data. Based on the writing score, students’ scores kept improving in every test. In the first cycle test, the mean of writing score was 61,43. In the second cycle test the mean of writing score was 75,13. Based on diary notes, observation sheet and questionnaire sheet, it was found that students were actively involved in writing process. The result of the research showed that Simultaneous Roundtable Strategy can improve students’ achievement in writing descriptive paragraph. Keywords: Simultaneous Roundtable, Writing, Dscriptive Paragraph, Action